Use of multiplex PCR for the diagnosis of Theileria annulata and Theileria buffeli - Altay, Kürşat; Aydin, Mehmet Fatih; Uluişik, U?ur; Aktaş, Münir; Dumanli, Nazir (My University, 2008)
The species causing theileriosis in cattle in Turkey are Theileria annulata and T. buffeli. While T. buffeli is low in pathogenicity or non-pathogenic , T. annulata is very pathogenic and causes tropical theileriosis with high morbidity and mortality in cattle. In this study, a multiplex PCR was used for a simultaneous diagnosis of these species. Genes for the merozoite surface antigen (Tams 1) and the major piroplasm surface protein (MPSP) were amplified with PCR for T. annulata and T. buffeli, respectively. It was found that both single and mixed infection with T. annulata and T. buffeli could be diagnosed with multiplex PCR.
Theileria annulata ve Theileria buffeli'nin Teşhisinde Multiplex PCR'in Kullanilmasi.
Keywords: Animals; Antigens, Protozoan; Cattle; DNA, Protozoan; Electrophoresis, Agar Gel; Polymerase Chain Reaction; Protozoan Proteins; Theileria; Theileria annulata; Theileriasis; major piroplasm surface protein, Theileria; parasite antigen; protozoal DNA; protozoal protein; Tams1 antigen; unclassified drug; agar gel electrophoresis; animal; animal disease; article; cattle; genetics; isolation and purification; methodology; parasitology; pathogenicity; polymerase chain reaction; Theileria; Theileria annulata; theileriosis